Focused Review: Agmatine in Fermented Foods - Galgano, Fernanda; Caruso, Marisa; Condelli, Nicola; Favati, Fabio (Frontiers in Microbiology, 2012)
Polyamines (PAs) are ubiquitous substances considered as bioregulators of numerous cell functions, being involved in cell growth, division and differentiation. These biogenic amines are also involved in tissue repairing and in intracellular signaling; in fact, because of their polycationic character, they interact strongly with membrane phospholipids and may play an important role in the regulation of membrane-linked enzymes. The intracellular polyamines content derives from the simultaneous regulation of their synthesis, catabolism, uptake and elimination; furthermore, PAs are present in all cell types at variable concentrations, but the highest levels are found in rapid-turnover tissues. In addition to spermidine, spermine and putrescine, also agmatine (AGM), deriving from arginine and identified in mammals in the 1990s, belongs to PAs and several studies have reported its possible positive role in secretagogues, neuronal, vascular, metabolic and therapeutic functions. Because of the low arginine decarboxylase activity (ADC) in mammalians, the amounts of AGM found in their tissues can be only minimally ascribed to an endogenous de novo synthesis by the ADC, while a substantial AGM portion can be of dietary origin. Several food products contain only small amounts of polyamines, while higher concentrations can be found in fermented foods. PAs could also be considered as indicators of freshness in fish and meat products, being these moieties produced during food storage, thus confirming the main role of microorganisms in their synthesis. Although many biological functions have been attributed to polyamines, high levels of these compounds in foodstuffs can have toxicological effects; however, the safe level of dietary polyamines intake has not yet been established. In this paper the presence of AGM in different foodstuffs is discussed, taking also into account the various factors affecting its presence and concentration.